Influence of the degree of compaction and plastic properties of expansively stabilized clay soil with a gypsum mix on the shear strength - Gati Sri Utami; Dewi Kusumaningrum; Salman Attamimi (Journal of Civil Engineering, Planning and Design, 2022)
The expansive soils have strong shrinkage capabilities, which negatively damage soil stability. Adding chemicals and gypsum materials is one approach to improving soil qualities. To measure soil parameters before and after mixing with gypsum material, soil analysis requires sieve analysis, Atterberg limits, standard proctors, and direct shear. The tests were carried out on 3 samples of gypsum mix, i.e. (5%, 10%, 15%) and aging of each soil for 10 days, 15 days, 20 days, 25 days. Initial soil characteristics: γd = 1340 g / cm3, shear strength Ø = 76.4 ° dan C = 0.071 kg / cm2, yield point = 69.07% and plasticity index = 45.02%. After adding 15% gypsum with a safe time of 25 days, γd = 1418 g / cm3, high shear Ø = 84.9 ° dan C = 0.441 kg / cm2, yield point = 47.94% and yield index = 11.94%. The stabilized density of the expanding soil influences the shear strength, the 5.6 ° increase in density takes advantage of the strong shear increase of Ø = 11.11% and C = 521.2%.